Sivelestat sodium alleviates sepsis-associated acute lung injury by inhibiting ferroptosis via the Nrf2/SLC7A11/GPX4 axis - Ying Wang; Xiaoling Xia; Yan Lu; ChengLiang Zhang; Yaqing Zhou; Jingjing Fan (PLoS ONE, 2026)
Objective This study was aimed to investigate the therapeutic efficacy and mechanism of Sivelestat sodium in sepsis-associated acute lung injury (SALI). Methods A rat model of SALI was established using the cecal ligation and puncture (CLP) procedure. After the model was established in rats, behavioral changes, abdominal conditions, and survival rates were monitored. Comparative analyses included arterial blood gas parameters, the lung wet/dry weight ratio (W/D), lung injury scores, histopathological damage assessment, inflammatory cytokine levels, oxidative stress marker levels, and Fe 2+ concentrations in lung tissue. The expression levels of Nrf2, SLC7A11, GPX4, ACSL4, and TFR1 proteins in pulmonary tissues were also evaluated. Results All rats in the sham group survived. The survival rates in the low-dose (SL), medium-dose (SM), and high-dose (SH) groups (60.0%, 73.3%, and 86.7%, respectively) were higher than those in the CLP group (53.3%), although the differences were not statistically significant. Compared to the Sham group, the CLP group showed significantly lower PaO 2 and PaO 2 /FiO 2 , higher lung wet/dry weight ratio and lung injury score, higher levels of TNF-α, IL-1β, and IL-6 in the lung tissue, lower levels of SOD and GSH, and higher levels of Fe 2+ and MDA. Additionally, the expression of Nrf2, SLC7A11, and GPX4 proteins was downregulated, whereas the expression of ACSL4 and TFR1 proteins was upregulated. Compared to the CLP group, the SL, SM, and SH groups showed higher PaO 2 and PaO 2 /FiO 2 ratios. The SM and SH groups showed lower lung tissue W/D ratios and lung injury scores, along with lower levels of TNF-α, IL-1β, and IL-6 in the lung tissue. In contrast, only the IL-6 levels were lower in the SL group. The SM and SH groups showed significantly higher SOD and GSH levels, along with considerably lower Fe 2+ and MDA levels. Notably, the SL group exhibited significant improvement only in arterial blood gas parameters and IL-6 levels, with no statistically significant differences observed in other indicators, indicating a dose-dependent response. In all Sivelestat sodium-treated groups, the expression levels of Nrf2, SLC7A11, and GPX4 proteins in rat lung tissue were upregulated, whereas the expression of ACSL4 and TFR1 proteins was downregulated. To validate the Nrf2 pathway, medium-dose Sivelestat sodium was administered with or without the Nrf2 inhibitor ML385. Sivelestat sodium upregulated total Nrf2, nuclear Nrf2, SLC7A11, and GPX4, and downregulated ACSL4 and TFR1. Co-administration of ML385 largely abolished these changes and blunted its protective effects on lung histopathology. Conclusion Sivelestat sodium ameliorates SALI in rats by inhibiting ferroptosis through regulation of the Nrf2/SLC7A11/GPX4 signaling pathway.